Nitric oxide derivatives and soluble plasma selectins in patients with myeloproliferative neoplasms - Cella, Giuseppe; Marchetti, Marina; Vianello, Fabrizio; Panova-Noeva, Marina; Vignoli, Alfonso; Russo, Laura; Barbui, Tiziano; Falanga, Anna (Thrombosis and Haemostasis, 2010)
Essential thrombocythaemia (ET) and polycythaemia vera (PV) are characterised by a high incidence of thrombotic complications due to highshear stress of the vessel wall, blood hyperviscosity and hypoxaemia, all factors responsible for chronic endothelial dysfunction and platelet and leukocyte activation. We evaluated the activation status of vascular cells in 18 consecutive ET and 14 PV patients by measuring the plasma levels of the nitric oxide derivatives (NOX) (i.e. nitrites and nitrates) and of soluble selectins of platelet (P-selectin), endothelial cell (P-selectin and E-selectin) and leukocyte (L-selectin) origin. The effect of hydroxyurea (HU) therapy on these parameters was also investigated. NOX were significantly (p<0.01) increased in ET patients treated with HU (11.5 ± 2.6 nM) compared to non-HU treated ET (1.41 ± 0.3 nM) and to controls (4.78 ± 2.49 nM). Multivariate analysis confirmed HU therapy as an independent predictor of higher NOX levels in ET. In addition, NOX significantly correlated with haematocrit. Plasma P-selectin was significantly elevated in ET (350 ± 40 ng/106 platelets) and PV (482 ± 53 ng/106 platelets) patients compared to controls (120 ± 8 ng/106 platelets). In PV, also E-selectin (23.8 ± 4.2 ng/ml) was significantly increased compared to controls (11.2 ± 1.1 ng/ml; p<0.01). P-selectin was significantly correlated to platelet (R=0.33; p=0.01) and leukocyte count (R=0.6; p=0.000), while E-selectin (R=0.34; p=.014) and sL-selectin (R=0.3; p=0.03) were correlated with leukocyte count only. In the multivariate analysis, NOX predicted increased levels of E-selectin in ET, but not in PV patients. Our data demonstrate that ET and PV are characterised by an altered pattern of soluble selectins and NOX. HU-mediated increase of NOMX levels could represent an additional antithrombotic mechanism of this drug.
Keywords: Nitric oxide; selectins; essential thrombocythemia; polycythemia vera; Hydroxyurea